Mix & match Dance from sea to sea reviewed - Barnes, Clive 1927-2008 (Dance Books Ltd., Alton,Hampshire (UK), 2003)
Review of Dance from sea to sea. PALABRAS CLAVE: Festival of International Dance 2003, Fancy Free, American Ballet Theater, Bolshoi Ballet, Miami City Ballet, The Four Temperaments, Adam Cooper, Sea of Troubles, San Francisco Ballet, Don Quixote, Kirov Ballet.